The presence of species of Pseudochironomus Malloch 1915 (Diptera: Chironomidae) in watercourses of Chaco Serrano Ecoregion (Argentina, South America) - Paggi, Analia Constancia (2015)
Male imagos of Pseudochironomus viridis (Kieffer) are redescribed and the immature stages are described and figured for the first time. During this study, larva and pupal exuviae associated to P. richardsoni (Malloch) were recorded for the first time for South America. The specimens were collected from a stream and a river in the Pampasic Hills System in the Chaco Serrano ecoregion of Argentina.